APOPTOSIS INDUCING ACTIVITY OF PHYLLANTHUS POLYPHYLLUS ON HUMAN CANCER CELL LINES - SWAPNA.G (SWAPNA GURRALA); B. RAJKAPOOR; BHARATHI KOGANTI; K.V.S.R.G. PRASAD (International Journal of Pharma and Bio Sciences, 2014)
The aim of this study was to investigate the apoptosis inducing property of methanolic extract of Phyllanthus polyphyllus (MPP) in vitro using human cervical cancer cells (HeLa) and human breast carcinoma cells (HBL-100). First, the anti-proliferative activity of MPP was determined using Tryphan blue dye exclusion method. Then, the apoptosis of cells was evidenced in MPP (500 µg/ml) by using propidium iodide (PI) staining and fluorescent microscopy. The Tryphan blue dye exclusion assay showed that MPP had induced a dose- dependent decrease in cell viability. The IC50 of MPP was found to be 340 and 250 µg/ml. Among the tested cell lines, MPP was more selective cytotoxic against HBL-100 than HeLa. Extensive apoptotic changes were found in HBL-100 and HeLa cells. The morphology of cancer cells induced by MPP after staining with PI and examined under a fluorescence microscope was condensed chromatin and fragmented nuclei.